О численном моделировании пространственного деформирования среды с сосредоточенной массой и расклинивающим давлением на пересекающихся включениях - Дейнека, В.С.; Белоус, М.В. (Видавничий дім "Академперіодика" НАН України, 2008)
A problem of modeling of the dynamic equilibrium of a medium with a localized mass and a disjoining pressure on thin intersecting inclusions is considered. The discontinuous FEM function classes are used to find the approximate generalized solution. Error estimates of the approximate solutions and the results of solving a model problem are presented.